Developing resilience to climate change impacts in Antarctica: An evaluation of Antarctic Treaty System protected area policy. Issue 124 (October 2021) - Hughes, Kevin A.; Convey, Peter; Turner, John
Highlights: Antarctic environments and biodiversity are vulnerable to climate change. Antarctic protected areas can help promote resilience to climate change impacts. Climate change is little considered in ATS protected area guidelines and agreements. Existing protected area management plans little consider climate change impacts. International efforts to enhance resilience and protection should be supported. Abstract: Antarctica is increasingly vulnerable to climate change impacts, with the continent predicted to warm by ∼4 °C by 2100 under a 'business as usual' greenhouse gas emission scenario. Simultaneously, human activity, primarily in the form of scientific research and the fishing and tourism industries, is putting increasing pressure on Antarctic and Southern Ocean environments and ecosystems. We evaluate the effectiveness of the Antarctic area protection system in promoting resilience to climate change impacts. Under the framework of the Antarctic Treaty System (ATS), terrestrial and marine areas can be designated to protect locations of scientific, environmental, historic and intrinsic value and to facilitate operational coordination to minimise environmental impact. However, climate change is not mentioned explicitly in the Protocol on Environmental Protection to the Antarctic Treaty and is little considered in guidelines for the designation and management of the region's existing protected areas. Climate change impacts are considered in only 17% of Antarctic Specially Protected Area (ASPA) management plans and, at a time when threats to Antarctic environments are increasing, the last decade has seen an 84% decline in ASPA designation rate compared with levels in the 1980s. Nevertheless, momentum is building within the Scientific Committee on Antarctic Research (SCAR) and the ATS's Committee on Environmental Protection (CEP) to deliver an evidence-based, integrated response to climate change that includes the use of protected areas. The Antarctic scientific community is well-placed to support decision-makers in the use of existing conservation management tools through provision of climate change forecasts at sub-regional scales, data on anticipated environmental change, and predicted species and ecosystems responses. Ultimately, reducing global greenhouse gas emission will provide the greatest protection from climate change impacts within Antarctica.